2020
DOI: 10.16995/traj.414
|View full text |Cite
|
Sign up to set email alerts
|

Fodder for Change: Animals, Urbanisation, and Socio-Economic Transformation in Protohistoric Italy

Abstract: In central and northern Italy, the first millennium BC was characterised by the rise of urbanism and an expansion of nearly every area of production. Agriculture was no exception, and an increase in the scale and intensity of agricultural production sustained, and was sustained by, economic and population growth. Within this context, animal management also evolved to meet the needs of the changing protohistoric landscape. Pigs grew in importance as meat producers, and a greater emphasis was placed on animal-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…Our results support the accepted chronology that chickens were present in Italy by the eighth century BC (Trentacoste 2020; Corbino et al . in press).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results support the accepted chronology that chickens were present in Italy by the eighth century BC (Trentacoste 2020; Corbino et al . in press).…”
Section: Discussionsupporting
confidence: 91%
“…Our results support the accepted chronology that chickens were present in Italy by the eighth century BC (Trentacoste 2020;Corbino et al in press). This is a similar timeframe to their arrival on the Balearic Islands, where a chicken bone has been directly dated to the eighth to sixth century BC (Ramis et al 2017).…”
Section: A Revised Spatio-temporal Pattern Of the Spread Of Chickenssupporting
confidence: 92%
See 2 more Smart Citations
“…The farming sites of the ancient Mediterranean communities, especially in the southern Italy communities of Magna Graecia, predominantly involved the breeding of sheep and goats, while pig husbandry progressively increased up to the Roman imperial age. 33 However, many reports have confirmed that cattle were domesticated some 10 500 years ago. 34 Consistently, a detailed proteomic analysis of calcified deposits in vessels from the ancient site of Çatalhoÿuk in Anatolia (ca.…”
Section: Proteomicsmentioning
confidence: 99%